Functional Outcomes of Fixation of the Scaphoid Fracture with Herbert Screw: A Cross-Sectional Study - Niaz Hussain Keerio, Muhammad Shuaib Chandio, Sajjad Hussain Bhatti, Zulfiqar Ali Jatoi, Farukh Hussain, Dost Muhammad Sohu (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The present study aims at the assessment of the radiological union and clinical outcomes of scaphoid fracture followed by fixation by Herbert Screw. Study design: A cross-sectional study Place and Duration: This study was conducted Muhammad Medical College and Hospital Mirpurkhas from may 2021 to may 2022 Methodology: A total of 20 patients were included in the study and all of them had sustained a scaphoid fracture. All of them were treated with Herbert screw fixation. Overall 18 of them were male and 2 were female. Serial radiographs were obtained for the assessment of union and the Modified Mayo wrist scoring (MMWS) system was used for the assessment of functional outcomes. The patients were called after 6 months of surgery for a follow-up visit. A total of 9 (45%) patients were treated within the first week of the injury. Overall 5 (25%) were treated in two weeks and 6 (30%) were treated in 2 to 4 weeks Results: Out of 20 patients included in the study, 17 had fractured at the waist of the scaphoid and the remaining 3 had sustained fractures at the proximal pole of the scaphoid. The dorsal and volar approach of fixation by Herbert Screw was used for treating all the fractures. A good alignment was observed post-operatively. Out of all the 20 patients, 12 (60%) patients showed excellent outcomes with a full range motion of the wrist, 6 (30%) had shown good results, and 2 (10%) showed poor results. A final follow-up was arranged during the sixth month of treatment and 18 (90%) patients showed adequate radiological union. Conclusion: Fixation of scaphoid fracture with a Herbert Screw in a convenient and effective mode of treatment which has shown excellent functional outcomes and exceptionally reduced complications. Keywords: Herbert Screw, Fixation, Functional outcomes, Scaphoid fracture